Candi Dermo Sebagai Pembelajaran Etnosains Di Sekolah Dasar - Fitanti, Sinta Yuni; Widodo, Wahono; Istiq'faroh, Nurul (Jurnal Ilmu Sosial dan Budaya Indonesia, 2024)
Through ethnopedagogy, education is designed to appreciate and integrate local knowledge, traditions, and unique ways of learning in the community. This study aims to explore the potential of Dermo Temple as a vehicle for ethnoscience learning at the elementary school level. Through a qualitative approach with a development research design, this study analyzes the potential of Dermo Temple in integrating scientific knowledge with local cultural values. Data were collected through interviews, observations, and questionnaires. The results of the study indicate that Dermo Temple has enormous potential as a learning resource rich in historical, cultural, and scientific values. The impact of this study is that there are two kalamakala statues and a winged human statue that were found and are currently in the Trowulan museum. Dermo Temple-based learning can increase students' learning motivation, develop critical thinking skills, creativity, and problem-solving abilities, and foster a love for the nation's culture and heritage. In addition, this study also highlights the importance of cooperation between schools, museums, and the community in developing sustainable learning programs. The conclusion of this study is that Dermo Temple is not only a historical site, but also a learning center that inspires the younger generation to appreciate and preserve the nation's cultural heritage.